Micromolded Polylactid Acid With Selective Degradation Rate - Iozzino, Valentina; De Meo, Annarita; Pantani, Roberto (Frontiers in Materials, 2019)
Poly(Lactic Acid), PLA represents an extremely interesting polymer for industrial applications because of its good processability, interesting physical properties, the possibility of being obtained from renewable sources, biocompatibility and biodegradability. The major depolymerization mechanism and the rate-controlling step of PLA biodegradation in compost is represented by the hydrolysis. The characteristic of being degradable is not per se an advantage: the propensity to degrade in the presence of water significantly limits specific industrial applications, particularly for durable products with long-term performance such as in the automotive, electronic, and agricultural industries, as well as in medical applications. Being able to control the degradation rate would be a real advantage: a product should preserve its characteristics during processing and for a time comparable to its application but should be nevertheless fully biodegradable at longer times. Furthermore, a gradient of properties could allow to produce samples in which some portions degrade at a faster rate and some others at a slower one. The degradation rate of PLA can be modified using several techniques, such as blending, copolymerization and surface modification. However, these change the physical properties of the material. Any factor affecting the rate of hydrolysis could either accelerate or retard the whole biodegradation process. The aim of this work is verifying the possibility to obtain samples with a degradation rate that can be modulated in time and at different rates within the same part, by using a technique to influence locally the morphology of the samples. Biphasic samples (half amorphous and the other half crystalline) were obtained by micro-injection molding and the degradation process was monitored by means of hydrolysis tests. The analysis confirmed the crystalline regions show a slightly better resistance to the hydrolysis compared to the amorphous.